Interaction of the Factor H Family Proteins FHR-1 and FHR-5 With DNA and Dead Cells: Implications for the Regulation of Complement Activation and Opsonization - Kárpáti, Éva; Papp, Alexandra; Schneider, Andrea E.; Hajnal, Dávid; Cserhalmi, Marcell; Csincsi, Ádám I.; Uzonyi, Barbara; Józsi, Mihály (Frontiers in Immunology, 2020)
Complement plays an essential role in the opsonophagocytic clearance of apoptotic/necrotic cells. Dysregulation of this process may lead to inflammatory and autoimmune diseases. Factor H (FH), a major soluble complement inhibitor, binds to dead cells and inhibits excessive complement activation on their surface, preventing lysis and the release of intracellular material, including DNA. The factor H-related proteins (FHRs) share common ligands with FH, due to their homology with this complement regulator, but they lack the domains that mediate the complement inhibitory activity of FH. Because their roles in complement regulation is controversial and incompletely understood, we studied the interaction of FHR-1 and FHR-5 with DNA and dead cells and investigated whether they influence the regulatory role of FH and the complement activation on DNA and dead cells. FH, FHR-1 and FHR-5 bound to both plasmid DNA and human genomic DNA, where both FHR proteins inhibited FH-DNA interaction. The FH cofactor activity was inhibited by FHR-1 and FHR-5 due to the reduced binding of FH to DNA in the presence of the FHRs. Both FHRs caused increased complement activation on DNA. FHR-1 and FHR-5 bound to late apoptotic and necrotic cells, and recruited monomeric C-reactive protein and pentraxin 3, and vice versa. Interactions of the FHRs with pentraxins resulted in enhanced activation of both the classical and the alternative complement pathways on dead cells when exposed to human serum. Altogether, our results demonstrate that FHR-1 and FHR-5 are competitive inhibitors of FH on DNA; moreover, FHR-pentraxin interactions promote opsonization of dead cells.